THE EFFECT OF THE QUANTUM TEACHING LEARNING MODEL SUPPORTED WITH FLIP CHART MEDIA ON THE ABILITY TO DESCRIBE THE APPEARANCE OF THE EARTH SURFACE IN THE SURROUNDING ENVIRONMENT IN THIRD GRADE STUDENTS OF SDN TANARU - Uri Harnani; Nuriasih Nuriasih; Baiq Nitri Srimuliani (Renjana Pendidikan Dasar, 2023)
The background of this research is direct interviews with Third-grades teachers at SDN Tenaru who have not used various models and learning media in teaching science subjects, especially regarding the basic competence of describing the appearance of the earth's surface in the surrounding environment. In teaching, they still use the old paradigm where the teacher gives knowledge to students passively with lecture and question and answer methods, so that classical learning completeness also cannot reach the minimum completeness criteria. The problems in this study are (1) is there any influence of the Quantum Teaching model supported by Flip Chart media on students' ability to describe the appearance of the earth's surface in the surrounding environment (2) is there any effect of the Quantum Teaching model without the support of Flip Chart media on the ability to describe the appearance of the earth's surface in the surrounding environment (3) is there a significant influence between the use of the Quantum Teaching model supported by Flip Chart media and the use of the Quantum Teaching model without Flip Chart media on the ability to describe the appearance of the earth's surface in the surrounding environment. Based on data analysis performed using descriptive quantitative data analysis techniques. Based on the results of the posttest in this study it can be concluded that (1) There is an influence of the Quantum Teaching model supported by Flip Chart media on the ability to describe the appearance of the earth's surface in the surrounding environment (2) There is an influence of the Quantum Teaching model without the support of Flip Chart media on the ability to describe the appearance of the earth's surface in surrounding environment (3) the results of the ability to describe the appearance of the earth's surface in the surrounding environment using the Quantum Teaching model supported by Flip Chart media without Flip Chart media is proven by t-count 3.916t-table 2.024 sig level (5%) so t-count > t- table with df 38 and sign (2-tailed) 0.000 <0.05 which means it is significant and the highest final score for the control class is 71.00 which is less than the final score for the experimental class 87.00